The Chernobyl – Thirty Years After The Post – Accidental Radiological – Hygienic and Medical Consequences - G. G. Onishchenko (Радиационная гигиена)
As the result of the Chernobyl NPP accident more than 200 thousand square kilometers of the European territories were contaminated by Cs-137 in the amount of above 37 kBq/m2 (1 Ci/km2 ). Belorussia, Russia and Ukraine amount up to 70% of this entire affected area. More than 600 000 people were engaged in the accidental cleanup operations, 340000 were evacuated or relocated within 1986-1991. The early stage evacuation efficacy is confirmed by the absence of acute radiation syndrome among the population and by the prevented collective dose which amounts to no less than 10 000 man/Sv. The effective measure to reduce the internal radiation dose to the population at the early accidental stage was introduction of maximum tentative permissive levels of radionuclide content in the foodstuffs.Among the identified post -accident medical consequences of the Chernobyl is the radiation syndrome found in 134 emergency cleanup workers within the first 24 hours of the accident’s development. Out of that number, 28 people died within the first four months, 19 people died before 2006. The accident’s liquidators developed radiation -induced leukemia ( the attributive risk value is 45-60% ). People exposed to high radiation doses display the statistically significant 18% morbidity increase of all types of solid cancers at the doses above 150 mSv. There is the statistically significant information indicating the increased amount of thyroid cancer morbidity among those who were just children and teenagers at the time of the accident. The adverse psychological consequences are accounted for not just the fear of overexposure but also for the disturbance of the habitual lifestyle especially mindful of the forced relocation.The longterm protection measures, radionuclide decay and selfcleaning of the contaminated areas resulted in the drastic reduction of the population dose in the radioactively contaminated territories. In 2015, only in some settlements of the Briansk Region’s the mean annual effective dose to the population exceeds 1 mSv. Presently the major goal is to transfer to normal human life with the change of the legal status of radioactively contaminated settlements in which the radiation situation is back to normal.The article provides the comparative data on the Chernobyl and the Fukushima - 1 accidental consequences and emphasizes the necessity of retaining the Chernobyl experience because the rapid advancement of the atomic energy around the world makes the mitigation of the accident’s consequences a truly international mission.